Pengukuran Beban Kerja Dan Penentuan Jumlah Tenaga Kerja Menggunakan Metode Full Time Equivalent Pada Proses Produksi Link Engine Hanger - Sri Lestari; Andri Oktarian; Okik Mardiansyah (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2024)
The Full Time Equivalent method is used to complete various jobs against the effective working time available. To get the FTE value of a work process must use Work load Analysis calculations using the equations of total activity time, allowance, and total available time. From research, it is known that overload workloads exist on fine boring workstations. The total number of FTE values on fine boring workstations is 1.38. Underload workloads are Clean Spatter 1 &; 2 stations and QC Inspection. At Clean Spatter stations 1 &; 2, the workload result for operator 4 is 0.46 and operator 5 the workload result is 0.48. For QC Inspection workstations, the workload result obtained is 0.89. From the results of workload equalization, the result is obtained that the total workload can be done with 6 operators. The workload balance value increased from the previous 76% to 88% or an increase of 12%.Keywords: Full Time Equivalent, Work Load Analysis, Allowance, Production process, Cycle time